Does Foreign Aid Cause "Dutch Disease"?: Case of Cambodia, Lao PDR, Myanmar and Vietnam - Lar, Ni; Taguchi, Hiroyuki; Sakurai, Hiroaki (Journal of Reviews on Global Economics, 2016)
This paper examined the economic impacts of foreign aid from the Dutch-Disease perspective, focusing on the economies of Cambodia, Lao PDR, Myanmar and Vietnam (so-called CLMV). The CLMV were targeted in this study since they have rarely been studied in the literature in this field although their economies have still depended highly on foreign aid. We found no evidence that they have suffered from the Dutch Disease, or rather identified a positive production effect of foreign aid. We speculate that the major use of foreign aid in the CLMV has focused on economic infrastructure, which has given little room for raising consumption and contributed directly to capital accumulation there.